Pendalaman Materi: Laporan Keuangan sebagai Dasar Analisis Investasi Saham - Ika Pratiwi Simbolon; Imas Nurani Islami; Vita Elisa Fitriana (ACADEMICS IN ACTION Journal of Community Empowerment, 2019)
This community service activities aims to deepen public understanding in making financial records and reporting correctly and making the financial statements as a basis for investment analysi. The investment analysis method used is a discounted cash flow model to determine whether the investment is undervalued or overvalued. The community in this activity are students of SMK Bina Nasional Informatika, North Cikarang. The implementation phase of this activity includes a field survey, coordination with the school principal, the implementation of a financial report socialization program as a basis for stock investment analysis, and preparation of the report. The socialization activity went smoothly attended by 28 Accounting students in class XII. Socialization participants seemed enthusiastic about the material provided. This can be seen from the beginning to the end of the event, all participants followed well. Based on the results of interviews, questions and answers and direct observations, community service activities have increased the knowledge of students by as much as 80% about how to prepare good financial statements and conduct stock valuations using financial statements.